A Study in Additive Manufacturing of Windings for Traction Machines - Estenlund, Samuel; Adolfsson, Erik; Hosseini, Seyed (International Symposium on Power Electronics, Electrical Drives, Automation and Motion, 2024)
This work presents a literature study over how additive manufacturing can be used to improve the performance of windings for traction machines when it comes to materials, loss minimization and thermal management, especially for concentrated windings. It continues to present the additive manufacturing methods most suitable for additively manufacturing windings. The lessons from manufacturing coils with metal binder jetting are presented, concluding that some support structures are needed which can be chemically removed later in the process which means that the full detail capability of metal binder jetting can not be utilized fully. Finally different approaches to thermal management with additively manufactured coils are modelled. The results show that compared to direct air cooled windings, additively manufactured copper coils with direct cooling can increase the maximum current by 50 %. If aluminium (AlSiMg) windings are made with both additive manufacturing and improved end-turn cooling they can match the performance of non-AM direct air cooled copper windings.